Comparison of the thermal comfort of pregnant women at different stages of pregnancy in a subtropical region. (1st July 2022) - Peng, Ting; Fang, Wenxiang; Jiang, Xiangyang; Yang, Yanping; Fang, Zhaosong; Zheng, Zhimin
Abstract: During pregnancy, owing to several physiological and psychological changes, the perception of heat by pregnant women changes, leading to them having different heat requirements. In this study, our objective was to determine the differences in the thermal perceptions of pregnant women at different stages of pregnancy (i.e., first, second, and third trimesters). Thus, we conducted an environmental parameter test on the obstetrics waiting rooms of four hospitals in Guangzhou and also administered a questionnaire survey to the waiting pregnant women. A total of 1043 questionnaires were collected during the survey (723 and 302 in summer and winter, respectively), after which the collected data was processed and statistically analyzed. Our results showed that with pregnancy development, the clothing resistance of pregnant women decreased, while their thermal sensation vote increased. Further, the mean neutral operative temperature values for the pregnant women in summer were 26.8, 25.2, and 24.1 °C, and in winter were 20.9, 19.6, and 18.9 °C during the first, second, and third trimesters, respectively. Furthermore, their preferred operative temperature values in summer were 25.8, 24.6, and 23.1 °C and in winter were 24.3, 24.0, and 22.8 °C during the first, second, and third trimesters, respectively. Thus, our results indicated that the perception of heat by pregnant women is dynamic, and increases with the development of pregnancy. These findings have guiding significance with respect to controlling the environment of the obstetrics waiting environments. Highlights: The thermal preferences of pregnant women at different stages were investigated. The pregnant women showed decreased clothing resistance with pregnancy evolution. Their neutral operative temperature also decreased with pregnancy evolution. The women preferred cool and warm environments in summer and winter, respectively.